Effect of kersen (muntingia calabura l) leaf decoction on perineal wound healing in postpartum women at Murniati Clinic Kisaran - Meity Christiani; Joharmi; Herviza Wulandary Pane (Science Midwifery, 2023)
Kersen is a traditional medicine. Kersen leaves have properties as antipyretic, anti-inflammatory, and even harmful antimicrobials and can be used as a natural antiseptic (Noorhamdani Yosef & Rosalia, cited by Salsabila. F, 2021). This research method uses the pre-experimental method, with the design of One Group Pretest-Posttes Without Control. The population of this study amounted to 32 postpartum women using the total sampling technique. The research instrument used an observation sheet. Data analysis techniques using descriptive analysis and chi-square test. The results of the study There is an effect of Kersen leaf decoction on perineal wound healing in postpartum women at the Murniati clinic in Kisaran in 2023, with a p-value = 0.000 (p <0.05). These results prove that kersen leaf decoction is effective in accelerating the healing of perineal wounds in postpartum women at the Murniati clinic in Kisaran, 2023. It is concluded that there is an effect of Kersen leaf decoction on the healing of perineal wounds in postpartum women. The suggestion of this study is that health services and health workers, especially midwives, are expected to provide education and practice to postpartum women about the use of Kersen leaf decoction for healing perineal wounds so that postpartum women can understand the benefits and disadvantages of not treating perineal wounds.